PHARMACEUTICAL INVENTORY MANAGEMENT ANALYSIS & OPTIMIZATION AT RSKD DADI MAKASSAR - Akram Ardi, Mohammad
Universal health coverage means that all people have access to the health services they need, when and where they need them without financial hardship. Before releasing the resolution of the WHA, the Indonesian government had issued a National Social Security System Act to provide a complete and integrated social protection for the community in 2004 created by the Social Security Organizing Agency through Law Number 24 of 2011 concerning the Social Security Organizing Board. With this Law, 2 (two) BPJSs are formed they are BPJS Kesehatan & BPJS Ketenagakerjaan. The presence of BPJS made the number of hospital patients increased sharply. That is because patients who have paid BPJS contributions every month feel entitled to receive health services from minor illness to severe illness. The increasing number of BPJS participants every year has made increasing demand for medicines that are included in the Formulary national category. These problems are mainly adding potential risk for the stock medicines. Stockout condition where the medicine supply in the warehouse is empty and unable to meet the increasing patient needs & understock condition where the medicine supply in the warehouse is below the standard hospital needs. Pharmaceutical Item planning in pharmacy RSKD Dadi has been using the method of consumption. The pharmaceutical medicine used for inpatient and outpatient pharmacy, including in Formulary National and Hospital, then forwarded the procurement process to review every week. This method is not accurate because it cannot provide data on demand, stock turnover and safety stock. The use of the consumption method at RSKD Dadi based on consumption by patient and units, so when the pharmacy warehouse is running low, procurement will be carrying out. It also supported that patented and generic medicine's total inventory turnover ratio is 9.23 in 2019, still below the ideal standard of 10-23 times. This problem influence by undesirable conditions such as excess purchases of items, government regulations or interference, and items from suppliers are out of stock. From the search for causal factors, there are several leading causes. There are inaccurate safety stock, unclear order quantity & no evaluation for demand. In the proposed inventory control system, two combined systems are suitable for classifying medicines item classes with ABC-VEN classification & a continuous review system for medicine with category I. Based on the analysis result, it can be concluded that hospital management can specifically make an inventory level savings potential of Rp 109.131.623- & value of Inventory turnover ratio increase from 10.30 to 20.5 on overstock item Category I. The hospital can raise from the actual estimated service level of 93.17% to 99.00% from the service level side. From simulation with actual daily demand on first-quarter obtained potentially save an inventory level by reduced by -27.22% with 99.91% Service level. This study proves that as long as the hospital can run & implement the policy for a long time, the inventory turnover ratio will be increased as long as the inventory level can be used minimally and efficiently.